Asymptomatic presentation of giant liver abscess: simultaneous Klebsiella pneumoniae and amoebic infection in an immunocompetent comorbid patient - Altwiher, Rasheed; Alzaid, Ahmed; Osman, Amir; Alhabeeb, Yasser; Alrdaian, Dareen; Almesmar, Nourah (International Surgery Journal, 2024)
Liver abscess is a rare clinical entity, giant abscess is also rare and asymptomatic presentation in immune competency is even rare. Simultaneous Klebsiella pneumoniae and amoebic liver abscess is rarely reported in immunocompetent patients, just few articles. Our case, a 69-year-old man was discovered to have hypoechoic liver mass during a scan of the abdomen for evaluation of dysuria. He was hospitalized through ER for advanced assessment. Systemic inquiries of the patient revealed generalized fatigue, constipation, but no fever, chills, abdominal pain or hypotension. Physical examination revealed normal liver span and no right upper quadrant tenderness. Tumor markers were not strikingly high and an enhanced abdominal computed tomography showed a large area of low attenuation with some liquefaction in the liver. Echo-guided aspiration revealed 220 ml of pus, which grew Klebsiella pneumoniae, and the same organism was isolated from the blood. Cytology examination of the pus showed scattered amoeba. The patient gradually improved over 3 weeks on treatment with meropenem and metronidazole, along with sustained drainage of the abscess cavity. No parasite ova or amoeba were found in the stool. He had no evidence of immunocompromise. Parasitic diseases may be a predisposing factor for bacterial infections, including pyogenic liver abscess. Giant size, possible coexistence of amoebae and bacteria in a liver abscess and asymptomatic presentation should not be discounted.